MODERN MODELS AND DEVELOPMENT PROSPECTS OF LEGAL EDUCATION AND PRACTICE COOPERATION IN UZBEKISTAN - AMINOV, Dalerjon (YURIST AXBOROTNOMASI, 2026)
This article scientifically analyzes theoretical models for the development of legal education and practice cooperation in Uzbekistan. The study covers the history, characteristics and role of the cluster approach, the “Triple Helix” model, clinical-practical and dual education models in the legal education system. The advantages of each model in improving the quality of legal training, the mechanisms of integration with practice and the socio-economic significance are revealed. The article also presents scientific conclusions on the prospects for the implementation of these models in the conditions of the Uzbek education system and ways to increase their effectiveness. The article also studies the experience of legal personnel training in developed foreign countries and shows how they can be used in Uzbekistan. The ways of cooperation between educational institutions, state organizations and private enterprises, as well as the role of legal clinics in student practice, are analyzed. The author gives practical suggestions and recommendations on improving the system of education in the field of law, properly organizing both study and work (dual education) of students, and training modern personnel who meet the requirements of the current labor market.